Evaluation of Pandemic Influenza A (H1N1) Pneumonia Patients Followed up in Intensive Care Unit from the Perspective of COVID-19 - Yilmaz, Pakize Ozciftci; Ozturk, Barcin; Kagnici, Ali Riza; Deniz, Mustafa; Sert, Ali Ihsan; Sahin, Ongun; Karaman, Can; Kurt, Ibrahim (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Influenza A (H1N1) virus have been a serious problem in 2009, which was considered as a pandemic and caused the death of more than 12000 people. Pneumonia is the most common complication of influenza infection and can be seen as viral pneumonia and/or bacterial coinfection. However, since November 2019, the world has been exposed to a new pneumonia agent named SARS - CoV - 2 from the Coronavirus family. In this case series, we aimed to re-evaluate the cases we followed up in the intensive care unit due to severe pandemic Influenza A infection between November 2019 and March 2020 from the Covid-19 perspective. Cases: There were five cases diagnosed with pandemic influenza A (H1N1) pneumonia in intensive care between November 2019 and March 2020, and the average age was 50. Given the risk factors two patients had immunosuppression and two patients had diabetes. Fever, respiratory distress and cough were the most prominent symptoms, and involvement in both lungs was detected in all patients on radiological imaging. Unfortunately, all patients had died despite antiviral therapy, antibiotic treatment against secondary bacterial infection, hemodynamic and respiratory support treatments. Discussion: Considering the literature, covid-19 and influenza co-infections have been detected in 34 cases since November 2019. In general terms, covid-19 and influenza tables are similar, with slight differences. In this case we look back to our findings, similar cases are considered as covid-19 under current conditions.